Coaching Activity And Its Practical Significance In The Pedagogical Process - Dallakyan, Armine; Martirosyan, Naira; Shaqaryan, Karine (Զանգակ հրատ.)
The article analyzes the peculiarities of coaching as pedagogical technology. That activity is presented in the context of a coach′s internship. Pedagogical science is the key to the development of modern society, which implies that the education system must be transformed in line with the changes of time. Coaching as a pedagogical technology ensures the learner's personal growth based on planning his own strategy. Therefore, the use of coaching as a pedagogical technology is relevant and in demand in modern schools, as it reveals the maximum potential of all learners and helps them develop cognitive-metacognitive abilities. The coach creates conditions for self- development by guiding the learners' educational needs, goals and potential opportunities.
Keywords: Pedagogy